Hadis tentang Syukur Bermakna Produktivitas - Aidah Putri Pratiwi; Zahrotun Nisa; Dadah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about gratitude. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about gratitude in Muslim history No. 5318. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Muslim No. 5318 is relevant to be used as a motivation to increase the productivity of the younger generation of Muslims in the country as a form of gratitude for the various potentials that Allah SWT has given so as to create prosperity in Indonesia.